E-commerce in Vietnam: Current Practice and Legal Solutions - Anh, Nguyen Hoang (VNU Journal of Science: Legal Studies; Article in press, 2026)
This article analyzes the current development of e-commerce in Vietnam from a legal perspective, based on an assessment of market size, market structure, and the level of completeness of the existing legal framework. The findings indicate that, despite maintaining a high growth rate, Vietnam's e-commerce sector continues to exhibit several structural challenges: i) a high level of market concentration in a small number of foreign platforms; ii) uneven development across regions; iii) widespread legal violations and persistent shortcomings in consumer protection; iv) the lack of specificity in the legal framework governing cross-border e-commerce activities; v) limited effectiveness in tax administration. The Law on E-commerce 2025 represents a significant step toward establishing a more unified and modern legal framework for e-commerce. However, this study argues that the law's effectiveness will largely depend on its concretization through implementing regulations and on the capacity for practical enforcement. On this basis, the article proposes a set of legal reforms aimed at strengthening platform regulation, enhancing enforcement effectiveness, promoting the use of technology in monitoring and supervision, and expanding international cooperation in the governance of cross-border e-commerce.